Representações do cuidador familiar frente as dificuldades vivenciadas no cuidado ao portador de TRM - COSTA, Marly Ramos da Silva (2019)
The spinal cord injury is a severe disabling syndrome, with significant neurological disorders. It is characterized by neurovegetative disturbances of body segments located below the injury by changes in motility, the superficial and deep sensitivity, although the SCI does not necessarily evolve to death, but limits and cause complete change in style and life choices of person affected. The increasing rate of traffic accidents and urban violence contribute to the increase of people with serious neurological damage in the spine, a phenomenon with direct impacts on the relationship of dependence on their victims with nursing care in a hospital environment, and especially in post-discharge withfamily caregivers. This study aims to analyze the difficulties experienced by family caregivers in patient care with TRM after hospital discharge, identifying the main complications resulting from spinal cord injury, addressing the importance of family caregivers in day to day and rehabilitation patient with TRM and offer as a tool, a guide to basic care to the primary caregiver of patients suffering with TRM. It is a study with data collection performed tir ¬ pair of secondary sources, by Surveying Library ¬ graph. This study has a descriptive and exploratory, conducted from March to November 2011. The role of family caregiver is of paramount importance to address the limitations and react in the pursuit of balance impairment, disability, handicap and health of clients, preparing it for the gradual achievement of functional gains and independence for daily activities and self-care. Therefore, it was observed in the study, the importance and necessity of health professionals at all levels of care, technical support, guidance and monitoring of local family caregivers and patients so that they feel safe and supported in the task of caringand be careful. We recommend our guide for the family caregiver guidelines in order to help them as far as possible, to provide a more appropriate care for their relatives with spinal trauma. We offer this work to all academic and professional community, hoping to expand the existing knowledge and bring together the database of scientific literature, a more updated about the theme.